Understanding of the Hadith on riba Among the Lecturers of Hadith at UIN Sumatera Utara Medan and its Relevance to the Modern Economy - Annisa Billah (Kopertais Wilayah III Yogyakarta, 2026)
The transformation of the modern economy, marked by the development of various financial products and services, such as conventional banking, credit cards, and digital-based loans, has given rise to debate regarding their suitability with Islamic sharia principles, particularly regarding the concept of usury. Differences in understanding of hadiths on usury also influence how Muslims view contemporary economic practices. In this context, the perspectives of hadith lecturers, as academics with scientific authority, are important to examine to provide a comprehensive understanding of the relevance of hadiths on usury to modern economic dynamics. This study aims to analyze the understanding of hadith lecturers at UIN North Sumatra Medan regarding hadiths on usury and examine their relevance to modern economic practices. This research used a qualitative method with a case study approach. Data were obtained through in-depth interviews, observation, and documentation with three hadith lecturers at UIN North Sumatra Medan. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the hadith lecturers understand usury as an additional requirement in debt transactions and its prohibition according to the Qur'an and hadith. In understanding the hadiths on usury, the informants used a textual and contextual approach, enabling them to connect the content of the hadiths with contemporary economic realities. Interest on online loans, credit cards, and conventional banks is seen as linked to the concept of usury (riba). This study concludes that the hadiths on usury remain relevant as a normative basis for assessing various modern economic practices to ensure they align with the principles of justice and Islamic sharia values. Keywords: Hadith on Riba, Understanding Hadith, Sharia Economics, UINSU Lecturer.